Удосконалення алгоритму повного групового розсилання у системах оброблення даних з розподіленою архітектурою - Кришталь, Р. П.; Лаврів, О. А.; Хархаліс, З. М. (Видавництво Львівської політехніки, 2016)
Поступове зміщення від індивідуальних до спільних платформ надання сервісів формує нові завдання, пов’язані з їх належним функціонуванням. У роботі здійснено моделювання та проведено дослідження роботи методу повного впорядкованого групового розсилання. Наведено основи побудови логічних годинників. У результаті аналізу виявлено, що наявна реалізація методу не придатна для процесів з non-FIFO чергами подій, тобто не здатна адекватно функціонувати в сучасних умовах високих інтенсивностей надходження запитів на обслуговування. За результатами проведеного аналізу запропоновано удосконалений метод повного впорядкованого групового розсилання, здійснено моделювання його роботи та показано, що запропоновані зміни дають змогу знизити імовірність відмови в сучасних розподілених системах надання сервісів. The gradual shift from individual to shared service delivery platforms brings distributed service delivery systems to the forefront and the problems associated with their proper functioning. Performance of totally ordered multicasting method was modeled and studied in this paper. The analysis revealed that current realization of the method is not suitable for processing non-FIFO-queue events, thus is not able to function adequately in modern highintensity flow of service requests. Accordingly, improved method is proposed. The block diagram of this method is depicted in the paper. The simulation process is specified. Performance of modified totally ordered multicasting method was modeled according to this process and it is shown that proposed changes allow decreasing of failure rate in modern distributed service delivery systems. The paper shows the use of totally ordered multicasting method in real systems is complicated by the fact that it only works well in the channel FIFO. Because of this disadvantage, we propose improved method of totally ordered multicasting, which enables the synchronization process to survive, even if the message of sender process is lost. The improvement is to limit the waiting time for a response from all the processes addressed. This is to reduce the probability of failure of the process. However, the signaling information amount increases that circulates in the data network.
Improving of totally ordered multicast algorithm for distributed architecture data processing systems
Keywords: розподілена система; платформа надання сервісів; повна групова розсилка; distributed system; service delivery platform; totally ordered multicast